Wacana Kesetaraan Gender dalam Keluarga pada Film Nanti Kita Cerita tentang Hari Ini : Analisis Wacana Kritis Norman Fairclough - Naurah , Nabila Zalfa; Siregar , Rachmi Kurnia (Penerbit Goodwood, 2023)
Purpose: This study aims to find out how the discourse on gender equality in the family in the film